Archaeology and urban sustainability: Can the past provide a key to the future? - Söderström, Ulrika (International Planning History Society Proceedings, 2016)
Many of today´s challenges of how to create and plan for sustainable cities in the future holds similarities to those that urban residents and decision makers have been confronted with for centuries. Therefore it is often argued that the past can provide us with knowledge to understand some of these challenges and in this a number of interdisciplinary sciences have an important role to play. However, when it comes to archaeology and especially archaeological knowledge about past urban societies, this role is still explored to a limited extent. The question is: how can archaeological research on prehistoric urban landscapes and cities be useful when planning for and working with urban sustainability today? Can the past provide a key to the future? In a publication from 2014 Christian Isendal (Prof of archaeology at Univ. of Gothenburg) argue that even though urban researchers and planners have extensive knowledge about the history of cities and often refer to the historical dimension, their references in time and space are often limited. It is pointed out that one of the distinct contributions that archaeological urban research can provide is a unique long-term perspective and a broader set of diversified examples to use as a source for creative ideas when discussing urban development and working on finding solutions to urban problems today. In this paper I explore this long-term perspective and discuss how archaeological urban research can be used to point to factors that are central to, and which undermine, sustainable urban development. Drawing upon the conference´s main theme, this paper presents the urban vision of Västergarn, an early medieval settlement on the southwestern coast of Gotland (Sweden), and highlight some of the challenges to its urban development. As many of the cities around the world today, Västergarn showed remarkable resilience as the settlement responded to and recovered from contemporary crises and disasters. Yet its urban growth and development was proven unsustainable and subsequently led to de-urbanization. Through this example I aim to illustrate that archaeological research on prehistoric urban landscapes and cities has considerable potential if it is used for more than just providing a historical perspective on urban development. Rather it can increase our understanding of some of the issues and problems that planning and developing sustainable cities are confronted with now and in the future.